ASPEK-ASPEK KELISANAN DALAM PROSALIRIS PENGAKUAN PARIYEM KARYA LINUS SURYADI AG - Agus Kurniawan (Balai Bahasa Nusa Tenggara Barat, 2014)
The development of modern printed traditional arts is highly influcing the development of Indonesia literatures. The production phase from a traditional to amechanical industry affects to both the number of the literature productions and its supporting community. Tthe development of moderent printed media is also considered to signal the and of the classic literature tradition as well as the birth of a modern literature tradition. Moreover ,the invention of the printed machine production technique is also considered to end the oral tradition in Indonesia community as well as to start a new tradition,the script tradition.The easily accusable literature trigger literature trigger literature activities to leave spirit as in the oral tradition, in cartain condition ,it could be tolerated ,however Indonesian community is not totally leave out the oral tradition in their literature activity .this paper describes the path of folklore existing in literarature traditions in Indonesia community .by analyzing the lyrical prose of pengakuan perayem by linus suryadi Ag.,it is found out that the exiting of verbal aspects shows that Indonesia people have not totally moved to script literature .this research applies two theories ,namely are folklore theory by walter j.ong and hegemony theory by Gramsci, folklore the oral aspect in a text, while hegemony theory is used to expectcts in a text while hegemony theory is used to explain the oral aspects in a text, while hegemony theory is used to explain the oral aspects a Javanese perspective.